2015
DOI: 10.2108/zs140062
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Structure and Evolutionary History ofDrosophila ornatifrons(Diptera, Drosophilidae) from Atlantic Forest of Southern Brazil

Abstract: Drosoph1la ornatifrons of the guarani group (Diptera: Drosophilidae) is found mainly in humid areas of the Atlantic Forest biome, especially in the southern region of Brazil. Historical and contemporary fragmentation events influenced species diversity and distribution in this biome, although the role of paleoclimatic and paleogeographic events remain to be verified. The objective of the present study was to evaluate the demographic structure of D. ornatifrons from collection sites that are remnants of Atlanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 70 publications
1
1
0
Order By: Relevance
“…The influence of precipitation on the modelling strategies further supported the interference of the climatic oscillations of the Quaternary in the population dynamics of these species, since this period is characterized by alternating periods of dry and wet conditions in the Southern Hemisphere [ 97 , 98 ]. These results are also concordant with phylogeographic studies performed with other Brazilian drosophilids, which also showed signals of population expansion dated to the Pleistocene [ 99 101 ]. This general pattern suggests that several drosophilid species have been subject to demographic oscillations during the glacial–interglacial cycles of this Epoch [ 99 , 102 ].…”
Section: Discussionsupporting
confidence: 90%
“…The influence of precipitation on the modelling strategies further supported the interference of the climatic oscillations of the Quaternary in the population dynamics of these species, since this period is characterized by alternating periods of dry and wet conditions in the Southern Hemisphere [ 97 , 98 ]. These results are also concordant with phylogeographic studies performed with other Brazilian drosophilids, which also showed signals of population expansion dated to the Pleistocene [ 99 101 ]. This general pattern suggests that several drosophilid species have been subject to demographic oscillations during the glacial–interglacial cycles of this Epoch [ 99 , 102 ].…”
Section: Discussionsupporting
confidence: 90%
“…The inland Western Central populations seem to diverge from the Eastern Atlantic populations nearly 4,000 ya. America (Hd = 0.554) (Manfrin & Sene, 2006;Franco & Manfrin, 2013;Cenzi de Ré et al, 2014;Gustani et al, 2015;Barrios-Leal et al, 2018a, b).…”
Section: Phylogeographic History Of D Sturtevanti Mitochondrial Dnamentioning
confidence: 99%